Addressing climate change with a comprehensive US cap-and-trade system - Robert N. Stavins (Fondazione Eni Enrico Mattei (FEEM), 2008)
There is growing impetus for a domestic U.S. climate policy that can provide meaningful reductions in emissions of CO2 and other greenhouse gases. I describe and analyze an up- stream, economy-wide CO2 cap-and-trade system which implements a gradual trajectory of emissions reductions (with inclusion over time of non-CO2 greenhouse gases), and includes mechanisms to reduce cost uncertainty. Initially, half of the allowances are allocated through auction and half through free distribution, with the share being auctioned gradually increasing to 100 percent over 25 years. The system provides for linkage with emission reduction credit projects in other countries, harmonization over time with effective cap-and-trade systems in other countries and regions, and appropriate linkage with actions taken in other countries, in order to establish a level playing field among domestically produced and imported products.
Keywords: Q54; Q28; Q38; Q48; Q58; 330; Cap-and-Trade System; Carbon Dioxide; Greenhouse Gas Emissions; Global Climate Change; Carbon Taxes